Análise da imunoexpressão de pten e p-akt em queilites actínicas e carcinomas epidermóides de lábio - Rodrigues, Carolina Maia (2022)
Actinic cheilitis (AC) is a potentially malignant disorder that most often affects the vermilion of the lower lip, characterized by epithelial and connective tissue changes caused by chronic exposure to ultraviolet (UV) solar radiation. AC has been associated as a risk condition for the development of squamous cell carcinoma of the lip (SCCL), which represents 12% of all head and neck tumors. UV radiation is capable of causing DNA damage, mutations in tumor suppressor genes, changes in the cell cycle and disordered cell proliferation, which leads to dysplastic alterations and the development of SCCL. Recent research on the process of lip carcinogenesis seeks to identify biomarkers capable of better understanding the development of this process, which have the ability to predict the prognosis of SCCL as well as predictors of AC with greater potential for malignant transformation. The PTEN/PI3K/AKT cell signaling pathway, one of the most mutated in oral cancer, may also be involved in the carcinogenesis process of lip cancer. Thus, the objective of this research is to evaluate the immunoexpression of PTEN and pAKT oncoprotein in epithelial dysplasias (EDs), arising from AC lesions, and in SCCL s. 45 paraffin-embedded blocks were selected, referring to 25 incisional biopsies of ACs and 20 incisional biopsies of SCCLs. The sociodemographic results show that most patients with AC were male (n=20; 80%) and aged over the 4th decade of life (n=21; 84%). Most patients with SCCL were male (n=13; 65%) and aged over 40 years (n=20; 100%). Of these, 6 patients (30%) worked in an environment with chronic and continuous sun exposure. Regarding the histomorphological characteristics, most of the ACs presented mild ED (n = 14; 56%) and 11 (55%) well-differentiated SCCLs. PTEN immunostaining did not reveal statistical significance in the different cellular sublocalizations analyzed between ACs and SCCL s. No statistical significance was detected between the histopathological grades of malignancy (GHMs) of EDs and SCCL s with the different cellular sublocalizations of PTEN and p-AKT. There was a greater amount of PTEN cytoplasmic immunostaining than nuclear immunostaining in ACs (p = 0.0008) and SCCL s (p < 0.0001). A significant increase in cytoplasmic p-AKT was detected in SCCLs when compared to ACs (p = 0.0017). A greater amount of cytoplasmic than nuclear p-AKT was detected in SCCL s (p < 0.0001). Our findings provide evidence for the possible role of PTEN and p-AKT in the process of lip carcinogenesis.